PENGARUH UKURAN PEMERINTAH DAERAH, PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH, KOMPLEKSITAS DAERAH, DAN BELANJA MODAL TERHADAPKELEMAHAN PENGENDALIAN INTERNAL PEMERINTAH DAERAH (Studi Empiris Pada Kabupaten Dan Kota Di Provinsi Sumatera Utara Periode 2012-2015) - Lenni Mustika Sari; Desmiyawati Desmiyawati; Susilatri Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the influence of Local Government Size, Economic Growth, Region Own Source Revenue, Regional Complexity and Capital Expenditure On The Internal Control Weakness Of Regional Government. The population in this study are 33 regencies and cities of North Sumatera Province. This research uses secondary data in the form of BPK audit report, Population, PDRB Report, Realization Report of APBD, and data of sub-district. The examination has been done by using SPSS software 17.0 versions i.e. the examination of coefficient determination test, classic assumption test and multiple regressions analysis. The result of coefficient determination test shows that the contribution of all independent variables to dependent variable are 7.8% and the remaining 92.2% are influenced by other variables. The result of t test shows that local government size has no significant effect on the On The Internal Control Weakness Of Regional Government 0.411 > 0.05. Economic growth has no significant effect On The Internal Control Weakness Of Regional Government 0.806 > 0.05. Local Revenue has a significant positive effect On The Internal Control Weakness Of Regional Government 0.045 < 0.05. The Regional Complexity has no significant effect On The Internal Control Weakness Of Regional Government of 0.877 > 0.05. Capital Expenditure has a significant negative effect On The Internal Control Weakness Of Regional Government 0.040 < 0.05.Keywords : Local Government Size, Economic Growth, Region Own Source Revenue, Regional Complexity, and Capital Expenditure.